INVESTIGATING A PROFESSIONAL TEACHING of THE NEW LECTURER in INDONESIA - Muhammad Yunus; Ani Sari (IAIN Syekh Nurjati Cirebon, 2018)
The concern held on this issue vary in term of English language teaching practices especially teaching speaking by the new speaking lecturer of University of Islam Malang (Unisma). The descriptive qualitative study was then designed in order to describe the teaching speaking activities by the new speaking lecturer of Unisma. Twice classroom observatios were conducted in two different speaking classes. Moreover, the new lecturer and ten students from speaking II D & II E were also invited to join twice interviews. By the same token, simple questionnaires which consists of thirteen questions were also distributed to know students’ involvement during speaking class. From the investigation, it was found out that the new lecturer has implemented procedural teaching performances such as preparing teaching activities – designing lesson planning, teaching journal and course outline, executing the plans in classroom – creating group discussion, presentation and individual task, and assessing the progress after teaching and learning activities such as implementing oral test. Moreover, the observed students were motivated by the new lecturer teaching way. Additionally, the new lecturer only implemented ICT based learning as the supporting way to facilitate her teaching not as her main media.